Overcoming challenges in music education during the COVID-19 pandemic: A literature review - Bhardwaj, Nitish (2025)
Amid the tumultuous landscape of the COVID-19 pandemic, music education encountered unprecedented challenges, disrupting traditional teaching methodologies. However, educators devised innovative strategies to ensure the continuity of musical learning. This article delves into the multifaceted challenges faced by music educators during the pandemic, offering insights into their steadfast commitment and the effective solutions they employed. From navigating the transition to virtual learning to addressing inequities in access, this exploration showcases the indomitable spirit of music educators worldwide. Through their resilience, creativity, and adaptability, music educators not only overcame obstacles but also paved the way for a more resilient and inclusive future for music education.